SOSIALISASI PEMBUATAN SABUN PADAT DENGAN PENAMBAHAN EKSTRAK DAUN SERAI WANGI (Cymbopogon Nardus) (Universitas Bengkulu, 2024)
This socialization activity aims to enhance students' skills in producing solid soap enriched with citronella leaf extract (Cymbopogon nardus) as a form of contextual learning based on science and entrepreneurship. Citronella was chosen for its antibacterial properties and distinctive aroma, which add value to the soap product. The activity was conducted in a school environment, with students as the primary participants. The methods used included delivering materials on the benefits of citronella, extraction techniques, and the saponification process. The results of the socialization showed that students not only understood the basic chemistry theory behind soap-making but also successfully applied the techniques to produce solid soap with appropriate texture, fragrance, and quality. In addition to providing practical insights into chemistry, the activity also fostered students' creativity and entrepreneurial skills by introducing opportunities to develop natural product-based businesses. This activity serves as an effort to promote innovative and practical learning in schools while increasing students' awareness of the sustainable utilization of local resources. Keywords: solid soap, citronella, Science-based learning, saponification